PENGARUH KONDISI BATUAN TERHADAP KIMIA AIR TANAH DI DAERAH KOTA JAYAPURA DAN SEKITARNYA - , Bodian Davin Panggabean ST ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Groundwater is clean water source which mostly used for many kind of purposes such as household/domestic purposes (drinking, bathing, and washing), agricultural purposes, and industrial purposes. There are specific requirements for each purposes. These requirements include physical, chemical and bacteriological requirement. Physical and chemical charactheristic of groundwater depends on the lithological condition where the groundwater is located. In this case, my research is conducted in in Jayapura and surrounding area. The purpose of this study is to determine the type, class of groundwater based on ion content in groundwater and determine the relationship between the condition of the rock toward the chemical content in groundwater in Jayapura area. This study took ten sampling locations, and the sampling method was stratified random sampling. Sample location was determined based on the unit formation on regional geological maps and sample point selected randomly. Samples taken from springs dug wells and bore wells. In interpreting the influence of rock conditions on the chemical content of groundwater in the study area, four methods were used: classification kurlov method, trilinier piper diagrams, stiff diagrams patterns, and barcollins methods. Test parameters among other is pH, Temperature (T0C), TDS, Hardness (CaCO3) as physical-chemical testing of groundwater, Magnesium (Mg), Calcium (Ca), Potassium (K), Sodium (Na), Sulfate (SO4), Chloride (Cl) and Bicarbonate (HCO3) as a chemical test groundwater. While the chemical test to determine the type of mineral rock made with X-Ray testing Difraction (XRD). Results of the study showed that: 1) Study area have 4 classes of groundwater namely (a) Class groundwater Magnesium - Bicarbonate, (b) Calcium-Magnesium - Bicarbonate, (c) Calcium-Magnesium - Bicarbonate, (d) Calcium-Bicarbonate. 2) The most dominant cations and anions in the study area are Magnesium and Bicarbonate, which based on the lithological type of aquifer, Magnesium derived from graywacke rock solution and rocks which rich contain of magnesium such as dunite, schist, gneiss, filit. Bicarbonate solution derived from carbonate rocks such as limestone, dolomite, and sand-clay. In connection with the morphology and lithology, chemical condition of groundwater in research areas can be summarized as follows: 1). Type of chemical constituents of groundwater in the study area can be divided into three classes, namely Mg-HCO3, Ca-Mg-HCO3 and Ca-HCO3. 2a). Influence of morphology on groundwater chemistry content can be divided into 2, namely: a. In terrain morphology, groundwater chemistry class is Mg-HCO3 s/d Ca-Mg-HCO3 with TDS content range from 310-452 mg/L and Cl- between 2.94-7.15 mg/L. b. In hill morphology groundwater chemistry class among other Ca-HCO3, Ca-Mg-HCO3 and Mg-HCO3 with TDS content range from 65-280 mg/L and Cl- between 0.12-0.90 mg/L. From this could be concluded that TDS and Cl- content towards plain is greater. 2b). Influence of lithology on the chemical constituents of groundwater can be classified into 3 namely: a. In the sand-clay sediments groundwater chemistry class is Mg-HCO3 s/d Ca-Mg-HCO3. with TDS content ranges from 310-452 mg/L and Cl- between 6.62-7.15 mg/L. b. In the class of chemical sedimentary rocks are Mg-HCO3 groundwater s/d Ca-Mg-HCO3 with TDS content range between 167-351 mg/L and Cl-between 0.12-2.94 mg/L. c. In igneous rocks, groundwater chemistry class are Mg-Ca-HCO3, Ca-HCO3 and Mg-HCO3 with TDS content range from 65-166 mg/L and Cl- between 0.12 to 0.49 mg/L. Based on the three lithological condition, it could be seen that TDS and Cl- content is greater on sedimentary rocks than in igneous rocks.